Framing Climate Goals in Terms of Cumulative CO2‐Forcing‐Equivalent Emissions. Issue 6 (26th March 2018) - Jenkins, S.; Millar, R. J.; Leach, N.; Allen, M. R.
Abstract: The relationship between cumulative CO2 emissions and CO2 ‐induced warming is determined by the Transient Climate Response to Emissions (TCRE), but total anthropogenic warming also depends on non‐CO2 forcing, complicating the interpretation of emissions budgets based on CO2 alone. An alternative is to frame emissions budgets in terms of CO2 ‐forcing‐equivalent (CO2 ‐fe) emissions—the CO2 emissions that would yield a given total anthropogenic radiative forcing pathway. Unlike conventional "CO2 ‐equivalent" emissions, these are directly related to warming by the TCRE and need to fall to zero to stabilize warming: hence, CO2 ‐fe emissions generalize the concept of a cumulative carbon budget to multigas scenarios. Cumulative CO2 ‐fe emissions from 1870 to 2015 inclusive are found to be 2, 900 ± 600 GtCO2 ‐fe, increasing at a rate of 67 ± 9.5 GtCO2 ‐fe/yr. A TCRE range of 0.8–2.5°C per 1, 000 GtC implies a total budget for 0.6°C of additional warming above the present decade of 880–2, 750 GtCO2 ‐fe, with 1, 290 GtCO2 ‐fe implied by the Coupled Model Intercomparison Project Phase 5 median response, corresponding to 19 years' CO2 ‐fe emissions at the current rate. Plain Language Summary: The relationship between the global average temperature anomaly (the difference between the global average current temperature and the global average preindustrial temperature) and the total quantity of CO2 emissions released is linear. However, contributions from other greenhouse gases mean that this simple relationship is lost. We propose a new way of comparing greenhouse gases by converting them into a "forcing equivalent" quantity of CO2 . This method means that the linear relationship between total CO2 ‐forcing‐equivalent (CO2 ‐fe) emissions and warming remains linear. This new greenhouse gas metric allows us to estimate the total CO2 ‐forcing‐equivalent emissions released over the industrialized period (1870–2015) as 2, 900 ± 600 GtCO2 ‐fe, and increasing at a rate of 67 ± 9.5 GtCO2 ‐fe/yr. Budgets of remaining CO2 ‐forcing‐equivalent emissions to key temperature stabilization goals are also estimated, showing that the CO2 ‐fe emissions metric is a useful way to characterize budgets to key temperature stabilization goals when considering multigas mitigation pathways. Key Points: We introduce the CO2 ‐forcing‐equivalent metric Estimation of CO2 ‐forcing‐equivalent emissions to date is presented Characterizing of multigas emissions scenarios and budgets in terms of CO2 ‐forcing‐equivalent emissions is shown